Epidemiology of periodontal disease in dogs in the UK primary‐care veterinary setting. (9th August 2021) - O'Neill, D. G.; Mitchell, C. E.; Humphrey, J.; Church, D. B.; Brodbelt, D. C.; Pegram, C.
Abstract : Objectives: Periodontal disease is a frequent diagnosis of dogs and can have severe negative impacts on welfare. It was hypothesised that breeds with skull shapes that differ most in conformation from the moderate mesocephalic skull shape have higher odds of periodontal disease. Materials and Methods: The cohort study included a random sample of dogs under primary veterinary care in 2016 from the VetCompass Programme database. Risk factor analysis used random effects multivariable logistic regression modelling. Results: The study included a random sample of 22, 333 dogs. The 1‐year period prevalence for diagnosis with periodontal disease was 12.52% (95% CI: 12.09 to 12.97). Eighteen breeds showed increased odds compared with crossbred dogs. Breeds with the highest odds included Toy Poodle (odds ratio 3.97, 95% confidence intervals 2.21 to 7.13), King Charles Spaniel (odds ratio 2.63, 95% confidence interval 1.50 to 4.61), Greyhound (odds ratio 2.58, 95% confidence interval 1.75 to 3.80) and Cavalier King Charles Spaniel (odds ratio 2.39, 95% confidence interval 1.85 to 3.09). Four breeds showed reduced odds compared with crossbreds. Brachycephalic breeds had 1.25 times the odds (95% confidence interval 1.11 to 1.42) of periodontal disease compared with mesocephalic breeds. Spaniel types had 1.63 times the odds (95% confidence interval 1.42 to 1.87) compared with non‐spaniel types. Increasing adult bodyweight was associated with progressively decreasing odds of periodontal disease. Clinical Significance: The high prevalence identified in this study highlights periodontal disease as a priority welfare concern for predisposed breeds. Veterinarians can use this information to promote improved dental care in predisposed dogs, especially as these dogs age.